Visualization of the Skeletal Muscle Stem Cell Niche in Fiber Bundles. Issue 10 (6th October 2021) - Schüler, Svenja C.; Dumontier, Simon; Rigaux, Jonathan; Bentzinger, C. Florian
Abstract: Skeletal muscle stem cells (MuSCs) reside in a complex niche composed of the muscle fiber plasma membrane and the laminin‐rich basal lamina surrounded by the microvasculature, as well as different supportive cell types such as fibro‐adipogenic progenitors residing in the interstitial extracellular matrix. Within the first few hours after tissue damage, MuSCs undergo cytoskeletal rearrangements and transcriptional changes that prime the cells for activation. Due to their time‐consuming nature, enzymatic methods for liberation of single muscle fibers with fully quiescent MuSCs are challenging. Moreover, during enzymatic digestion, important niche components including the microvasculature and the collagenous interstitial matrix are destroyed. Here, we provide a method for the visualization of MuSCs on muscle fibers in their intact niche. Our method relies on mechanical teasing of fiber bundles from fixed skeletal muscles. We demonstrate that teased muscle fiber bundles allow the investigator to capture a representative snapshot of the MuSC niche in skeletal muscle, and outline how stem cell morphology and different microenvironmental components can be visualized. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Isolation of fiber bundles Basic Protocol 2 : Immunofluorescence staining of MuSCs on fiber bundles Support Protocol : Preparation of Sylgard dishes